2021
DOI: 10.1098/rsif.2020.0881
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pulse wave propagation across stenoses and aneurysms: assessment of one-dimensional simulations against three-dimensional simulations andin vitromeasurements

Abstract: One-dimensional (1-D) arterial blood flow modelling was tested in a series of idealized vascular geometries representing the abdominal aorta, common carotid and iliac arteries with different sizes of stenoses and/or aneurysms. Three-dimensional (3-D) modelling and in vitro measurements were used as ground truth to assess the accuracy of 1-D model pressure and flow waves. The 1-D and 3-D formulations shared identical boundary conditions and had equivalent vascular geometries and material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 71 publications
3
20
0
Order By: Relevance
“…Firstly, the computational model used in the present study is a one-dimensional model rather than a three-dimensional model that should be more accurate in simulating blood flow in the presence of an AAA. Nonetheless, a recent study has demonstrated that onedimensional modelling of the large arteries is accurate compared to three-dimensional modelling to simulate PW propagation across AAA [60]. Secondly, in patients with AAAs, calcification and intraluminal thrombus usually occur within the AAA, which change the stiffness (both the elastic modulus and wall thickness) of the AAA and significantly influence the distribution of AAA wall stresses [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the computational model used in the present study is a one-dimensional model rather than a three-dimensional model that should be more accurate in simulating blood flow in the presence of an AAA. Nonetheless, a recent study has demonstrated that onedimensional modelling of the large arteries is accurate compared to three-dimensional modelling to simulate PW propagation across AAA [60]. Secondly, in patients with AAAs, calcification and intraluminal thrombus usually occur within the AAA, which change the stiffness (both the elastic modulus and wall thickness) of the AAA and significantly influence the distribution of AAA wall stresses [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“… 2017 ; Chakshu et al. 2020 ; Jin and Alastruey 2021 ). The numerical implementation of the pulse-wave propagation model employed here is outlined in Jones et al.…”
Section: Methodsmentioning
confidence: 99%
“… 2018 ; Carson et al. 2019 ; Jin and Alastruey 2021 ) and aneurysms (Sazonov et al. 2017 ; Chakshu et al.…”
Section: Methodsmentioning
confidence: 99%
“…As a second example, we considered a pathological configuration of aortic coarctation, that is a congenital defect consisting of a local narrowing of the aortic lumen (most commonly in the aortic arch). To this end, we considered an arterial segment of 126 mm endowed with a stenosis model [38], with a 30% stenosis halfway of its length. Terminal boundary conditions are given by an RCR Windkessel model.…”
Section: Stenotic Aortic Segmentmentioning
confidence: 99%